Novel bifunctional nanomaterials as probes for bioimaging - Teo, Shiang Min. (2009)
This work investigates the synthesis of bifunctional nanomaterials using two methods - doping of superparamagnetic Fe2O3 nanoparticles with Tb3+ via hydrothermal reaction, as well as direct deposition of Y2O3:Tb nanoparticles onto Fe2O3 nanoparticles. The nanoparticles produced by these two methods were investigated for their magnetic and fluorescent properties, in addition to their structural characteristics.